Análisis semiótico del Qhapac Ñan (Camino del Inca) en la percepción histórica de los habitantes de la parroquia Achupallas-Cantón Alausí durante el período enero-julio 2021. - Velasco Merchán, Diana Priscila (2023)
The main objective of this research work is the semiotic analysis of the Qhapac Ñan (Inca Trail) in the historical perception of the inhabitants of the Achupallas-Canton Alausí parish, based on theoretical foundations about semiotic analysis according to Umberto Eco as well as the collective imagination from the perspective of Edgar Morín. This project collects interviews from three experts on the subject and information obtained through the participant observation technique. With this information, we carry out the semiotic analysis of each element found on the Qhapac Ñan trail. Finally, the data obtained allowed the realization of the conclusions and recommendations. The Qhapac Ñan or Camino del Inca is an Andean road system that allowed the exchange of agricultural products (barter) from one province to another, from Chimborazo to Cañar or vice versa. This trail is of great historical importance for the inhabitants of the Achupallas parish since it is part of our cultural identity. The semiotic elements found: Apachetas de Tres Cruces, Culebrillas lagoon, Paredones, the face of the Inca and the llama, are closely related to the Inca and Cañari worldview, ancestors who inhabited and, in turn, built this path. Although the Inca Trail has been a bit forgotten, the history and value it possesses will last from generation to generation.